Use of Canva Application as a Promotional Content Design for MSME ActorsM - Sholeh, Muhammad; Suraya, Suraya; Rachmawati, Rr. Yuliana (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, small, and medium enterprises (MSMEs) need effective marketing strategies to increase product visibility and sales. One way to promote products is by using digital media, such as social media and websites. The problem that exists in MSME actors is that not all MSME actors have adequate graphic design skills. In efforts to overcome this, MSME actors can use applications that can be used to create content design easily and the results are good. One application that can be used is Canva. Canva is a graphic design tool that is user-friendly and easy to use even for beginners who do not understand content design. This application provides a variety of templates and features that allow users to create attractive visual designs. One of the activities to improve MSME players is training on the importance of promotion on social media. This effort was made by MSME players who are members of the Banyuwangi Family Association in Yogyakarta (IKAWANGI) in collaboration with the Informatics study program of the AKPRIND Institute of Science Technology to organize training to improve promotion through social media and create easy and attractive promotional content. The implementation method is carried out by training methods and direct assistance to MSME actors. Assistance includes providing directions for creating content using the Canva application.  In the context of MSMEs, the use of Canva can help businesses to create promotional content such as brochures, posters, invitations, business cards, and so on. Businesses can customize the design with their brand, adding text, images, and logos to create a unique and consistent design. In conclusion, the use of the Canva application can provide significant benefits for MSME players in creating attractive and effective promotional content. With Canva, MSME players can increase their digital presence and increase product sales.